A Nonlinear Model-Predictive Motion Planning and Control System for Multi-Robots in a Microproduction System with Safety Constraints and a Global Long-Term Solution - Wangmanaopituk, Suparchoek; Voos, Holger Voos; Kongprawechnon, Waree (Agriculture and Natural Resources, 2014)
The manufacturing of microsystems such as micromotors and micropumps among other examples is a very important emerging market. One big challenge in microproduction is mass customization, that is, the automated production of a large variety of products that are highly adapted to special customer needs in small batch sizes. These requirements call for a highly flexible manufacturing system. This study focuses on the multi-robot coordination of the resulting flexible microproduction system which is solved here by the application of a multi-agent system. Additionally, all robots additionally applied the proposed nonlinear model predictive control approach on a local real-time level to solve problems associated with path-following and collision avoidance in parallel, while also considering differential constraints on single robots, such as velocity constraints, in this specific application. The global longterm motion planning approach was also considered as an optimization problem.